A (r)evolução das exposições de Arte através da Realidade Virtual: Uma nova abordagem a um Modelo de Negócio Sustentável (Estudo Exploratório - Monarca, B.; Ferreira, P. A. (2018 13th Iberian Conference on Information Systems and Technologies (CISTI), 2018)
In recent years there has been a considerable evolution of technological capacity. One of these evolutions took place in computer generated images and in 3D environments, which allowed to create environments and three-dimensional situations more reliable and immersive. This exploratory study is based on the assumption that this technology can be used to develop new areas of business models that allow the drastic reduction of logistics costs and complex operations realted to the arts ehchibitions organization and the production and simultaneously maintain a socialization and an interaction close to the real, whether in a ludic, cultural or business perspective. This concept is applied to the artistic and cultural area, in particular to the temporary exhibitions through the placement inside a platform of 3D Models that allow to faithfully replicate bi or three-dimensional works simulating a physical exhibition.